2018
DOI: 10.1176/appi.ajp.2018.18010072
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Motion Processing in Schizophrenia and the Attenuated Psychosis Syndrome: Etiological and Clinical Implications

Abstract: Objective: The ability to perceive the motion of biological objects, such as faces, is a critical component of daily function and correlates with the ability to successfully navigate social situations (“social cognition”). Deficits in motion perception in schizophrenia were first demonstrated ~20 years ago but remain understudied, especially within the early, potentially prodromal, stages of the illness. The authors examined the neural bases of visual sensory-processing impairments, including motion, in schizo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(53 citation statements)
references
References 40 publications
11
42
0
Order By: Relevance
“…Together, these results suggest that the TPJ-pSTS response to motion is abnormal in SzP. These results are in line with previous behavioral findings about reduced sensitivity to motion in general (21)(22)(23) and facial expressions and other types of biological motion more specifically (24)(25)(26). The similarity of the pattern of motion-correlated activation through the pSTS with the face-emotion localizer activity suggests that most of the motion in the movies was related to facial expression motion.…”
Section: Discussionsupporting
confidence: 91%
“…Together, these results suggest that the TPJ-pSTS response to motion is abnormal in SzP. These results are in line with previous behavioral findings about reduced sensitivity to motion in general (21)(22)(23) and facial expressions and other types of biological motion more specifically (24)(25)(26). The similarity of the pattern of motion-correlated activation through the pSTS with the face-emotion localizer activity suggests that most of the motion in the movies was related to facial expression motion.…”
Section: Discussionsupporting
confidence: 91%
“…In sum our findings suggest that in the patients with schizophrenia the early visual perception dysfunction may play a critical role not only in the general perception of objects but also in the emotion recognition deficit. Thus, our results further support the growing evidence to the bottom-up model of disrupted cognition in schizophrenia, which indicate that early sensory deficit contribute to the impaired higher level dysfunction 14,15,33,34,38,40,82,84 .…”
Section: Discussionsupporting
confidence: 87%
“…analyzed the correlation between visual sensory function and face emotion recognition. They showed that reduced motion sensitivity correlated with impaired face-emotion recognition in patients with schizophrenia and attenuated psychosis 40 . Taken together, previous investigations indicate that altered magnocellular pathway function contribute to impaired facial affect recognition, however the exact neurobiological background is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Although SZ had also deficits in motion perception (Martinez et al, ), utilizing a staircase procedure to control performance accuracy for each subject, this study was able to specifically investigate the metacognitive deficit of decision uncertainty monitoring in SZ. In addition, the “decision‐redecision” paradigm in making decisions on the same problem twice in each trial could separate the neural system merely involving in the metacognitive process that merely occurred during the redecision phase from that of the decision‐making process that also occurred during the first decision‐making phase.…”
Section: Discussionmentioning
confidence: 99%